Therapeutic Advances in Multiple Sclerosis - Yang, Jennifer H.; Rempe, Torge; Whitmire, Natalie; Dunn-Pirio, Anastasie; Graves, Jennifer S. (Frontiers in neurology, 2022)
Multiple sclerosis (MS) is an autoimmune disease affecting the central nervous system that causes significant disability and healthcare burden. The treatment of MS has evolved over the past three decades with development of new, high efficacy disease modifying therapies targeting various mechanisms including immune modulation, immune cell suppression or depletion and enhanced immune cell sequestration. Emerging therapies include CNS-penetrant Bruton's tyrosine kinase inhibitors and autologous hematopoietic stem cell transplantation as well as therapies aimed at remyelination or neuroprotection. Therapy development for progressive MS has been more challenging with limited efficacy of current approved agents for inactive disease and older patients with MS. The aim of this review is to provide a broad overview of the current therapeutic landscape for MS.